Students’ conceptual understanding in analytic geometry of planes based on their prior mathematical ability - Negara, Habibi Ratu Perwira; Santosa, Farah Heniati; Fatimah, Ade Evi; Nasrullah, Ahmad (Mahesa Research Center, 2024)
Mathematical conceptual understanding is a fundamental skill that serves as a foundation for more advanced abilities, including reasoning, communication, connections, and problem-solving. However, this foundational skill is influenced by students’ prior mathematical abilities. Therefore, the objective of this study is to identify and describe differences in students’ mathematical conceptual understanding based on their prior mathematical abilities. This research employs a mixed-method approach, involving 87 purposively selected students enrolled in the Analytic Geometry in Planes and Space course. The research instruments include a mathematical conceptual understanding test and documentation of students’ prior mathematical abilities. Data were analyzed quantitatively using one-way ANOVA and qualitatively by exploring mathematical conceptual understanding across categories of prior mathematical abilities. The findings reveal that both quantitative and qualitative analyses indicate that students with high prior mathematical abilities demonstrate superior mathematical conceptual understanding compared to those with medium or low prior mathematical abilities.